The management of Monochorionic Monoamniotic (MCMA) twin pregnancy - Ernawati Ernawati; Jihan Qonitatillah; Agus Sulistyono (Universitas Airlangga, 2023)
HIGHLIGHTS Monochorionic monoamniotic (MCMA) twin pregnancy has a significant risk of perinatal morbidity and mortality, including intrauterine fetal death (IUFD). The risk of prematurity, the risk of death due to MCMA complications, the availability of the NICU, also high costs on preterm care were factors in deciding to terminate the pregnancy. The ideal time to deliver monochorionic twins in order to reduce the risks of cord entanglement, growth discrepancies, and intrauterine fetal death is still a point of controversy. Early diagnosis, intensive antenatal monitoring, patient and family decision would contribute to antenatal mortality reduction. ABSTRACT Objectives: To present the management of monochorionic monoamniotic (MCMA) twin pregnancy. Case Report: Advanced prenatal treatment has improved the prognosis for Monochorionic Monoamniotic (MCMA) pregnancies; however, there is still no agreement on how to handle MCMA twins. The authors report 2 cases of monoamniotic monochorionic twin pregnancies. In the first case, a 30-years-old primi pregnant woman detected MCMA at 14 weeks of gestation; no complications related to MCMA were found; she planned delivery at 32 weeks, but one of the babies died in the womb at 31/32 weeks pregnant, a live baby born by cesarean section. The second case was a 36-year-old pregnant woman, on her third pregnancy, diagnosed with MCMA after 12 weeks of pregnancy, no complications related to MCMA, the baby was born at 32 weeks pregnant, and both babies survived. The management was the same in both cases, but different outcomes were obtained; in case 1, the baby died allegedly due to cord entanglement, which could not be detected during pregnancy.